Word Order Variation in Spoken Saudi Arabic: A Pragmatic Approach - Alyami, Nasiba Abdulrahman (International Journal of Language and Literary Studies, 2025)
One aspect in which languages vary is their differing patterns of word ordering in sentences. Some languages follow a restrictive word order, whereas others allow a flexible word order that does not affect the semantics of the text. In the literature, the Arabic language is deemed one of the flexible or “free word order” languages, which allow both VSO and SVO word orders without changing a clause’s meaning. The present study aims to identify the pragmatic (morpholexical and discourse) factors that play a significant role in determining the variable subject-verb word order in spoken Saudi Arabic. A corpus-based approach was taken by collecting a sufficient amount of natural spoken Saudi utterances for analysis. The corpus contains data collected from six recorded Saudi Arabic TV interviews with Saudi personalities in which the guests related personal stories about their social and practical lives. A classification system proposed by Owens et al. (2009) was adopted as a study tool to distinguish between the diverse factors that may predict the variant word order in spoken Saudi Arabic and to determine whether any relationship exists between such factors. The study found that the distributions of SV and VS word orders in spoken Saudi Arabic are similar, with a slightly higher percentage in SV word order (58% SV vs. 42% VS), and that the morpholexical class of subjects significantly predicts word order. The findings also indicate that discourse-pragmatic functions play an important role in predicting word order.